Antithrombotic drugs and subarachnoid haemorrhage risk - Pottegård, Anton; Rodríguez, Luis Alberto García; Poulsen, Frantz Rom; Hallas, Jesper; Gaist, David (Thrombosis and Haemostasis, 2015)
The study objective was to investigate the relationship between use of antithrombotic drugs and subarachnoid haemorrhage (SAH). We identified patients discharged from Danish neurosurgery units with a first-ever SAH diagnosis in 2000 to 2012 (n=5,834). For each case, we selected 40 age-, sex- and period-matched population controls. Conditional logistic regression models were used to estimate odds ratios (aOR), adjusted for comorbidity, education level, and income. Low-dose aspirin (ASA) use for < 1 month was associated with an increased risk of SAH (aOR 1.75, 95% confidence interval [CI] 1.28–2.40). This aOR decreased to 1.26 (95%CI: 0.98–1.63) with 2–3 months of ASA use, and approached unity with use for more than three months (1.11, 95%CI 0.97–1.27). Analyses with first-time users confirmed this pattern, which was also observed for clopidogrel. ASA treatment for three or more years was associated with an aOR of SAH of 1.13 (95%CI: 0.86–1.49). Short-term use (< 1 month) of vitamin K-antagonists (VKA) yielded an aOR of 1.85 (95%CI 0.97–3.51) which dropped after 3+ years to 1.24, 95%CI: 0.86–1.77. The risk of SAH was higher in subjects in dual antithrombotic treatment (aOR 2.08, 95%CI: 1.26–3.44), and in triple antithrombotic treatment (aOR 5.74, 95%CI: 1.76–18.77). In conclusion, use of aspirin,clopidogrel and VKA were only associated with an increased risk of SAH in the first three months after starting treatment. Long-term aspirin use carried no reduced SAH risk. Results should be interpreted cautiously due to their observational nature.
Keywords: Anticoagulants; aspirin; clopidogrel; platelet aggregation inhibitors; subarachnoid haemorrhage